Recent Progress in Quasi/All-Solid-State Electrolytes for Lithium–Sulfur Batteries - Yang, Shichun; Zhang, Zhengjie; Lin, Jiayuan; Zhang, Lisheng; Wang, Lijing; Chen, Siyan; Zhang, Cheng; Liu, Xinhua (Frontiers in Energy Research, 2022)
Lithium–sulfur batteries have received increasing research interest due to their superior theoretical capacity, cost-effectiveness, and eco-friendliness. However, the commercial realization of lithium–sulfur batteries faces critical obstacles, such as the significant volume change of sulfur cathodes over the de/lithiation processes, uncontrollable shuttle effects of polysulfides, and the lithium dendrite issue. On this basis, the lithium–sulfur battery based on solid-state electrolytes was developed to alleviate the previously mentioned problems. This article aims to provide an overview of the recent progress of solid-state lithium–sulfur batteries related to various kinds of solid-state electrolytes, which mainly include three aspects: the fundamentals and current status of lithium–sulfur solid-state batteries and several adopted solid-state electrolytes involving polymer electrolyte, inorganic solid electrolyte, and hybrid electrolyte. Furthermore, the future perspective for lithium–sulfur solid-state batteries is presented. Finally, this article proposed an initiation for new and practical research activities and paved the way for the design of usable lithium–sulfur solid-state batteries.